KAJIAN ARKEOLOGIS KOMPLEKS MAKAM DI BENTENG LIWULAKUDO - Riswan Riswan (SANGIA: Jurnal Penelitian Arkeologi, 2018)
The purpose of this study was to determine the shape of the tomb,variations in the shape of the tomb and to find out how the pattern of tomb placement. The results of this study show the forms of tombs in the Liwu Lakudo fortress, Lakudo subdistrict, Central Buton regency consisting of the form of jirat, tomb form, variation of tombform and tomb placement pattern. The shape of the jade consists of a square shape of stone pile, a jade of stonewithout adhesive, jade of stone arrangement with adhesive, and other forms of tomb. The tomb form consists ofround head shape, oval round, human face, irregular shape, and wood tombstone. Placement patterns tend to linear-ly follow the home network. The factors that influence the placement of the tomb are property rights factor, socialstrata, relationship and family.